Common corporate tax base in the EU : Impact on the size of tax bases and effective tax burdens - Spengel, Christoph (ZEW Economic Studies)
The European Commission envisages putting forward a proposal for a tax reform that would allow improving the efficiency and simplicity of the corporate income tax systems. This report assesses the impact of a Common Corporate Tax Base (CCTB) on the size of the corporate tax bases of EU companies. The results of the report shall help to evaluate the economic consequences of the introduction of a harmonised set of tax accounting rules. The estimates are based on the European Tax Analyzer with data from the year 2006 and apply options specified by the Commission's Steering Group.